2019
DOI: 10.1016/j.chom.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Bacteriophages Is Linked to Aggravated Intestinal Inflammation and Colitis

Abstract: Graphical Abstract Highlights d Bacteriophages target specific bacteria and mitigate bacterially driven colon cancer d Phages activate phage-specific and non-specific IFN-g mediated immune responses via TLR9 d Phages exacerbate colitis, and TLR9/IFNg blockade abrogates phage-mediated inflammation d UC patient responses to fecal microbiota therapy correlate with Caurovirales abundance SUMMARY Bacteriophages are the most abundant members of the microbiota and have the potential to shape gut bacterial communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
397
2
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(419 citation statements)
references
References 65 publications
11
397
2
9
Order By: Relevance
“…Bacteriophages, the most abundant members of the microbiota, activate IFN‐γ‐mediated immune responses via TLR9. Consistently, TLR9/IFN‐ γ blockade abrogates phage‐mediated inflammation (Gogokhia, et al , ). Elevated levels of circulating inflammatory cytokines, such as TNFα, IL‐6 and CRP (C‐reactive protein), are potent inducers of intestinal permeability (Sandek, et al , ; Al‐Sadi, et al , ; Al‐Sadi, et al , ), which can promote a vicious feed‐forward cycle of heightened endotoxin translocation and inflammatory cytokine accumulation in the circulation (Fig.…”
Section: The Link Between the Gut Microbiota And Cvd‐related Risk Facmentioning
confidence: 99%
“…Bacteriophages, the most abundant members of the microbiota, activate IFN‐γ‐mediated immune responses via TLR9. Consistently, TLR9/IFN‐ γ blockade abrogates phage‐mediated inflammation (Gogokhia, et al , ). Elevated levels of circulating inflammatory cytokines, such as TNFα, IL‐6 and CRP (C‐reactive protein), are potent inducers of intestinal permeability (Sandek, et al , ; Al‐Sadi, et al , ; Al‐Sadi, et al , ), which can promote a vicious feed‐forward cycle of heightened endotoxin translocation and inflammatory cytokine accumulation in the circulation (Fig.…”
Section: The Link Between the Gut Microbiota And Cvd‐related Risk Facmentioning
confidence: 99%
“…For phages, presuming they act by modulating the bacterial community, the animal model must harbor the relevant bacterial host species, and thus the bacterial microbiome may need to be manipulated as well. Notably, some recent studies have suggested that phages may also interact directly with eukaryotic host cells [28,29]. Overall, significant effort and resources must be expended to establish robust animal-infection models suitable to define the role of the virome.…”
Section: The Need For Experimental Animal-infection Modelsmentioning
confidence: 99%
“…A seminal study that incorporated an open‐label pilot of FMT explored the role of bacteriophages in altering mucosal immune responses. In this study, 20 patients with active UC treated with a single colonoscopic infusion of FMT showed a positive correlation between CD4 + T cell production of IFN‐γ from rectal mucosal biopsies and the relative abundance of total gut viral reads, specifically the bacteriophage Caudiovirales . They found that this bacteriophage was significantly enriched in patients who failed to respond to FMT.…”
Section: Immunological Mechanistic Insights For Fmt From Clinical Stumentioning
confidence: 80%